PENERAPAN TEORI BELAJAR BEHAVIORISTIK DALAM MEMBENTUK KARAKTER RELIGIUS SISWA MELALUI PROGRAM SHALAT ZHUHUR BERJAMA’AH DI SDN 10 CUBADAK AIR KOTA PARIAMAN - Irfansyah; Deliani, Nurfarida; Batubara, Juliana (Cahaya Ilmu Bangsa Institute, 2024)
This study discusses the formation of religious character in students of SDN 10 Cubadak Air through the congregational zhuhur prayer program in terms of behavioristic learning theory. Where this theory emphasizes changes in behavior that appear as a consequence of learning outcomes with its famous pattern, namely stimulus-response. In this study, researchers focused on the pattern of forming students' religious character through the congregational Zhuhur prayer program implemented in the school used as a research site, these educational programs and patterns will be juxtaposed with behavioristic learning theory. researchers used a qualitative approach in this research with a descriptive type of research, researchers conducted direct observation (observation), interviews with principals, teachers and documentation, the data obtained were analyzed using triangulation. The results showed that with the application of behavioristic learning theory in shaping the religious character of students through the congregational zhuhur prayer program is able to form student responsibility for their obligations in worship, able to change the morals of students who were previously not good to be better because of good habituation from starting to wash to remembrance after prayer, making students more directed, and the establishment of collaboration between educational units and with student guardians on the development of their children's behavior at school.